Sustainability : a history - Caradonna, Jeremy L., 1979- (Oxford University Press, 2014)
The word is nearly ubiquitous: at the grocery store we shop for ""sustainable foods"" that were produced from ""sustainable agriculture""; groups ranging from small advocacy organizations to city and state governments to the United Nations tout ""sustainable development"" as a strategy for local and global stability; and woe betide the city-dweller who doesn't aim for a ""sustainable lifestyle."" Seeming to have come out of nowhere to dominate the discussion-from permaculture to renewable energy to the local food movement-the ideas that underlie and define sustainability can be traced back sev